Spirometry and PRAM severity score changes during pediatric acute asthma exacerbation treatment in a pediatric emergency department - Arnold, Donald H (2012)
OBJECTIVES: To examine time-dependent changes of spirometry (percent-predicted FEV(1)[%FEV(1)])and the Pediatric Respiratory Assessment Measure (PRAM)during treatment of acute asthma exacerbations. STUDY DESIGN: We conducted a prospective study of participants ages 5–17 years with acute asthma exacerbations managed in a Pediatric Emergency Department. %FEV(1) and the PRAM were recorded pretreatment and at 2 and 4 hours. We examined responses at 2 and 4 hours following treatment and assessed whether changes of %FEV(1) and of the PRAM differed during the first and second 2-hour treatment periods. RESULTS: Amongst 503 participants, median [IQR] age was 8.8 [6.9, 11.4], 61% were male and 63% African-American. There was significant mean change of %FEV(1) during the first (+15.4%; 95%, CI 13.7, 17.1; P<0.0001) but not during the second 2 hour period (+1.5%; 95% CI −0.8, 3.8; P=0.21), and of the PRAM during the first (−2.1 points; 95% CI −2.3, −1.9; P < 0.0001) and second (−1.0 point; 95% CI −1.3, −0.7; P < 0.0001) 2 hour periods. CONCLUSIONS: Most improvement of lung function and clinical severity occur in the first two hours of treatment. Amongst pediatric patients with acute asthma exacerbationsthe PRAM detects significant and clinically meaningful change of severity during the second 2-hours of treatment, whereas spirometry does not. This suggests that spirometry and clinical severity scores do not have similar trajectories and that clinical severity scores may be more sensitive to clinical change of acute asthma severity than spirometry.